On conformal invariants in problems of constructive function theory on sets of the real line - Andrievskii, V.V. (Український математичний вісник, 2004)
This is a survey of some recent results by the author and his collaborators in the constructive theory of functions of a real variable. The results are achieved by the application of methods and techniques of modern geometric function theory and potential theory in the complex plane.